STRATEGIES TO IMPROVE COMPLIANCE WITH ANNUAL INDIVIDUAL TAXPAYER TAX RETURN (WPOP) REPORTING - Nasihin, Ihsan; Purwandari, Dian; Lasmini, Lilis; Kartika, Erawati; Andriansyah, Hendri Nur (Universitas Muhammadiyah Tangerang, 2025)
One of the obligations of taxpayers is to submit an Annual Tax Return (SPT) for both individuals and entities. The number of Taxpayers submitting Annual Tax Returns at the Primary Tax Service Office is still low. The aim of this research is to identify strategies that can be implemented to increase individual taxpayer compliance with their tax obligations, especially the Annual Tax Return. Data collected using interview and observation methods. The population in this research is Individual Taxpayers (WPOP) registered at one of the Pratama KPPs who have not yet or are late in reporting their Annual SPT as well as employees at one of the Pratama KPPs, namely Account Representatives (AR). The data analysis used in this research is data triangulation in order to find relevant results. The research results show that the factors for individual taxpayer non-compliance in reporting annual SPT are taxpayer awareness, use of e-filing applications, and tax socialization media. The strategy that can be carried out by one of the KPP Pratama is to increase compliance with the annual SPT report by conducting socialization about tax obligations, conducting socialization about how to use e-filling, imposing tax sanctions on individual taxpayers who are negligent and do not report taxes, and optimizing the use of technological media in socializing the obligation to report Annual Tax Returns for individual taxpayers. The theoretical and policy implications of the research are that it can provide empirical evidence regarding the factors that cause non-compliance in individual taxpayers' annual SPT reporting and strategies that need to be implemented to increase individual taxpayer compliance in reporting annual SPT